Awareness in innovators: From "outside the box" to "inside the bubble" - Prateek Goorha; Jason Potts (Journal of Global Entrepreneurship Research, 2016)
Innovation is sometimes perceived as a linear and sequential process, and at other times as multidimensional. Based on the common thread of 'awareness' that grounds many theories on innovation, we analyze the idea that a flexible informational awareness accounts for both perceptions within the same overall innovation strategy. To show this, we propose using a simple theoretical setup that yields an intuitive and tractable visualization - in the form of thought bubbles - for the process of innovation. We discuss the application of this visualization to the process of idea search and to the types of knowledge commons.
Keywords: 650; Innovation; Sequentiality; Multidimensionality; Ideas; Thought bubbles; Knowledge commons